The effect of oil feed pressure on friction and cavitation in plain bearings - Mansoor, Yousuf Ali (2018)
Experimental and theoretical studies of the influence of oil supply pressure on the friction torque in plain bearings have been carried out. The focus of the work has been the reduction in bearing friction that might be achieved by reducing oil supply pressure and the mechanisms by which the changes in friction occur, with potential applications to reducing bearing friction in internal combustion engines. A single bearing test rig has been used to investigate the impact of feed oil pressure on the extent of cavitation and the role of increased film cavitation on friction under light, steady loads for a bearing with a 180° groove, using an SAE 5W-30 oil. Film visualization shows that cavitation area increases when the oil feed pressure is reduced and the extent of the full width film reduces primarily as the angle of film reformation is retarded. Both load and speed increases reduce the full width film extent. At constant film viscosity, friction torque was reduced by up to 20% by increased cavitation which reduced the film area and the eccentricity ratio. The latter reduces the surface shear stress in the load-bearing region of the film and overall, the circumferential average. As load increases, the reduction in film area accounts for an increasing proportion of the friction torque reduction. The effect of load, speed, lubricant formulation and clearance on bearing friction and film pressure has been investigated. Increases in load led to increases in friction and peak film pressures with smaller percent reductions in friction torque as the supply pressure was reduced. Bearing friction torque was found to show a linear dependence on oil viscosity in the hydrodynamic regime where friction could be substantially reduced by using low viscosity oils. The effect of increased clearance was to reduce bearing friction and increase peak film pressures. The effects of reduced oil supply pressure on friction in crankshaft main bearings during cold-start warm-ups have been investigated. Friction reductions have been found to be most significant during cold running conditions at light loads. The thermal coupling between the bearing films and engine structure influences the film warm-up. Initially there is a rapid rise in film temperatures after which the warm-up is held back by the temperature of the surrounding metal. In addition to reducing bearing friction, reducing oil supply pressure also reduces the oil pumping work required; this represents an additional benefit which can be particularly significant under cold operating conditions.